Monitoring modeling and analysis of the electromagnetic environment of HVDC transmission lines based on ion flow and wind coupling field - Qin, Ziyi; Chen, Jiong; Ren, Maoxin; Yin, Fan (Frontiers in Energy Research, 2025)
High-voltage direct current transmission lines are an integral part of the power system, but the ion flow field and total electric field they generate can be harmful. Moreover, two of the most critical indicators for evaluating environmental compatibility, ion current density ρj and total electric field strength E, can be affected by wind. The difficulty in monitoring and modeling the ion flow and wind coupling field has caused recent research to consider only transverse winds and not take into account the wind directions. As a result, it cannot model the actual situation accurately for monitoring and analysis. For this reason, this article takes the ±800 kV Jinsu Line in Huzhou as an example and constructs a 3-D monitoring model using the finite element method. The nonlinear mapping relationship between the model design parameters and the feature parameters is approximated by an extreme learning machine, and the actual measurement results are used to invert the model design parameters to modify the finite element model and realize the precise monitoring of the ρj and E in different wind speed and direction situations. The results show that the modified model can realize the condition monitoring of the electromagnetic environment of transmission lines with an improved accuracy of 20.86%. In addition, some laws are discovered: the peak absolute values of ρj and E increase and then decrease with the increase in wind speed; at low wind speed, the smaller the included angle between the wind direction and the line direction is, the smaller the peaks are; at high wind speed, the smaller the included angle is, the peaks increase and then decrease.